Ravulizumab use for acetylcholine receptor-positive generalized myasthenia gravis in clinical practice - Katyal, Nakul; Govindarajan, Raghav; Goyal, Neelam; Muley, Suraj; Muppidi, Srikanth (Frontiers in Neurology, 2024)
Purpose: To describe the early experience of ravulizumab use in acetylcholine receptor antibody-positive generalized myasthenia gravis (AChR+ve gMG).Methods: This multicenter retrospective study included AChR+ve gMG patients who were treated with ravulizumab and had both pre-and post-ravulizumab myasthenia gravis activities of daily living (MG-ADL) scores.Clinical information regarding MG history, concomitant treatment(s), MG-ADL, other MG-specific measures, and adverse events were recorded.Results: A total of 18 patients with mean age of 61.83 (±16.08, n=18) years were included in this cohort. In 10 complement inhibitor naive patients, a clinically meaningful reduction in mean Mg-ADL (baseline: 6.6 (±3.58) vs 4.4 (±2.28), post ravulizumab) was seen. Six out of 10 patients (60%) had clinically meaningful reduction post ravulizumab and two achieved minimum symptom expression (MSE). In 8 patients switched from eculizumab to ravulizumab, further reduction was noted in post ravulizumab mean MG-ADL (Baseline: 3.25 (±3.34) vs 1.5 (±2.34) post ravulizumab). None of the patients who switched from eculizumab to ravulizumab experienced worsening symptoms. Eleven out of 14 (78.5%) patients on prednisone therapy were able to reduce their prednisone dose postravulizumab. None of the patients experienced any major side effects.In our clinical practice, 60% of AChR+ve gMG complement inhibitor naive patients experienced a clinically meaningful improvement in MG-ADL scores with ravulizumab. Patients were safely switched from eculizumab to ravulizumab and had further improvement in their mean MG-ADL scores. Of those on prednisone therapy, the majority were able to reduce their prednisone dosage.